2020
DOI: 10.3390/jcm9082472
|View full text |Cite
|
Sign up to set email alerts
|

GlycA Levels during the Earliest Stages of Rheumatoid Arthritis: Potential Use as a Biomarker of Subclinical Cardiovascular Disease

Abstract: This study aimed at evaluating the clinical relevance of glycoprotein profiles during the earliest phases of rheumatoid arthritis (RA) as biomarkers of cardiovascular (CV) risk and treatment response. Then, GlycA and GlycB serum levels were measured using 1H-nuclear magnetic resonance in 82 early RA patients, 14 clinically-suspect arthralgia (CSA), and 28 controls. Serum glycosyltransferase activity was assessed by a colorimetric assay. Subclinical CV disease was assessed by Doppler-ultrasound. We found that G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“… 28 The NMR signals for GlycA at δ 2.03 and GlycB at δ 2.07 were integrated and significant intensity differences were found between groups, with SARS-CoV-2 positive samples containing the highest median concentrations of both GlycA and GlycB, followed by SARS-CoV-2 negative samples ( Figure S2 ). GlycA has been shown to be a robust marker of inflammatory and proinflammatory conditions including inflammatory bowel disease, 29 gestational diabetes, 30 alcoholic liver disease, 31 cardiovascular risk, 32 rheumatoid arthritis 33 and certain cancers, 28 although GlycA is confounded by hemolysis and is not an appropriate marker of inflammatory conditions such as sickle cell disease. 34 In general, GlycA has been found to be a better predictor of inflammatory conditions than either C reactive protein (CRP) or interleukin-6 (IL-6), and is independent of both, although GlycA and CRP have been found to be strongly correlated in many studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 28 The NMR signals for GlycA at δ 2.03 and GlycB at δ 2.07 were integrated and significant intensity differences were found between groups, with SARS-CoV-2 positive samples containing the highest median concentrations of both GlycA and GlycB, followed by SARS-CoV-2 negative samples ( Figure S2 ). GlycA has been shown to be a robust marker of inflammatory and proinflammatory conditions including inflammatory bowel disease, 29 gestational diabetes, 30 alcoholic liver disease, 31 cardiovascular risk, 32 rheumatoid arthritis 33 and certain cancers, 28 although GlycA is confounded by hemolysis and is not an appropriate marker of inflammatory conditions such as sickle cell disease. 34 In general, GlycA has been found to be a better predictor of inflammatory conditions than either C reactive protein (CRP) or interleukin-6 (IL-6), and is independent of both, although GlycA and CRP have been found to be strongly correlated in many studies.…”
Section: Resultsmentioning
confidence: 99%
“… 34 In general, GlycA has been found to be a better predictor of inflammatory conditions than either C reactive protein (CRP) or interleukin-6 (IL-6), and is independent of both, although GlycA and CRP have been found to be strongly correlated in many studies. 28 Kettunen et al reported GlycA to be predictive of mortality risk in angiography patients 31 and has also been shown to be an early predictor of subclinical cardiovascular disease and treatment response in the early stage of rheumatoid arthritis 33 and in the development of gestational diabetes. 30 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…28 The GlycB acetyl signal (δ 2.07) arising from glycoprotein Nacetylneuraminidino groups has also been observed to increase in various inflammatory conditions such as diabetes and obesity. 29 Both GlycA and GlycB have been shown to correlate with C-reactive protein (CRP) levels in plasma, 17 and it has been suggested that GlycA and GlycB may be superior biomarkers of systemic inflammation over CRP, the main clinical chemistry marker of inflammation. 19,29 We recently reported that GlycA and GlycB are significantly elevated in COVID-19 patients and are strong markers of disease positivity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Particularly, the scientific interest and number of studies demonstrating the strength of the NMR glycosylation profile as a biomarker for systemic inflammation has exponentially grown since the last decade [17]. Glycosylation has been associated with the increased risk of cardiometabolic diseases [18], cancer, and the worst evolution of non-communicable [19][20][21] and communicable diseases [22], even after its adjustment for other inflammatory markers and in pathological processes and biological conditions that are different in nature, such as immune alterations [23] and functional hyperandrogenism or obesity [24], which share the common thread of low grade inflammation.…”
Section: Introductionmentioning
confidence: 99%